IMPLEMENTASI PEMBINAAN TAHSIN QUR’AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA/I SMAN 2 KLARI - Tia Febbiyanti; Haerudin; Herdian Kertayasa (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Implementation of Qur'an tahsin guidance in improving the Qur'an reading ability of students of SMAN 2 Klari. "This research aims to explain the implementation of tahsin coaching the Qur'an to help students at SMAN 2 Klari become better readers of the Qur'an. The foundation of this research is the importance of teaching students to read the Qur'an correctly in accordance with the rules of tajweed as part of character education and the strengthening of students' Islamic values". Qualitative descriptive research methodology uses documentation, interviews, and observations as data collection methods. The results of the study show that tahsin coaching is often carried out using the iqro method which emphasizes the determination of makhraj and tajweed. This exercise uses digital and printed Qur'an mushaf and is carried out in the classroom under the supervision of an Islamic Religious Education teacher. The application of this coaching has been proven to be effective in improving students' understanding of the basics of tajweed as well as the fluency and determination of hijaiyah letters when reading the Qur'an. This study recommends that tahsin coaching programs continue to be developed in a sustainable manner and supported by special training for supervisors.